DRINKING WATER PURIFICATION WITH OZONATION PROCESS IN UJJAIN CITY (M.P.) - khode, sheetal; Dalal, Dr.Parag (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
The primary goal of my project “Drinking water treatment by ozonation process” is to protect health of mihuman beings with the help of supplying water without dangerous viruses and pathogens and other harmful micro pollutants.  By this project an effort of supplying water with acceptably very low concentrations of microbial and chemical contaminants is imposed. For this purpose ozone is a strong oxidant and having a powerful disinfectant quality. It has been used in drinking water treatment for close to hundred years (Rakness, 2005).